Multiply each side by (x-1) and (x+2)
2(x+2) + 3(x-1) = 2 (x-1)(x+2)
2x+4 + 3x -3 = 2x^2 +2x -4
0= 2x^2 -3x -5
0=(2x-5)(x+1)
so x = 5/2 or x = -1
2006-11-06 11:55:27
·
answer #1
·
answered by MollyMAM 6
·
1⤊
0⤋
Most of these answers are false. it cannot equal 5 because if u plug it in would give u an answer of .9285. what u do is multiply all of the equation by (x-1)(x+2) which gives u
2x+4+3x-3=2x²+2x-4
you then combine the terms and get
2x²-3x-5=0
you factor and get
(2x-5)(x+1)=0
then u set them both equal to 0
2x-5=0 and x+1=0
and get
x=5/2,-1 as answers
2006-11-06 20:17:03
·
answer #2
·
answered by kiyomidog 2
·
1⤊
0⤋
5=x
2006-11-06 19:55:23
·
answer #3
·
answered by J 6
·
0⤊
2⤋
Multiply both sides by the common demoninator:
2(x-1)(x+2)/(x-1) + 3(x-1)(x+2)/(x+2) = 2(x-1)(x+2)
Simplify:
2(x+2) + 3(x-1) = 2(x^2+x-2)
Distribute
2x+4+3x-3 = 2x^2+2x-4
Simplify again
5x+7 = 2x^2+2x-4
2x^2-3x-11 = 0
then factor to find x (its not factorable, so you'll need to use quadratic formula)
2006-11-06 19:54:15
·
answer #4
·
answered by dreamgal 8 1
·
0⤊
2⤋
Command
Solve, showing approximate solutions to 6 digits.
Equation
1+ 5/x = 2
Varible
x
Result
Exact
Solution 1 (real)
x = 5
Approximate
Solution 1 (real)
X = 5.
2006-11-06 20:06:20
·
answer #5
·
answered by Anonymous
·
0⤊
1⤋
2/x-1+3/x+2=2
5/x+1=2
5/x=1
x=5
2006-11-06 19:57:46
·
answer #6
·
answered by Karen M 2
·
0⤊
1⤋
xâ -2 or 1
Multiply both sides by (x+2)(x-1):
2(x+2)+3(x-1)=2((x-1)(x+2))
Distributive property:
2x+4+3x-3=2x^2+2x-4
Combine like terms:
5x+1=2x^2+2x-4
Subtract 5x and 1 to both sides:
2x^2-3x-5=0
Factoring:
(2x-5)(x+1)=0
x=-1 and 5/2
Check:
2(5/2)-5=0
5-5=0
0=0
-1+1=0
0=0
I hope this helps!
2006-11-06 20:23:31
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
2/x-1+3/x+2=2
add 1 and subtract 2 from each side
2/x+3/x=1
2/x+3/x=5/x
5/x=1
x=5
2006-11-06 19:55:04
·
answer #8
·
answered by BoredAtWork 2
·
0⤊
2⤋
5
-2
+1
*x
2+3
5=x
2006-11-06 19:53:54
·
answer #9
·
answered by man of questions 3
·
0⤊
2⤋
You have to get a common denominater for those two fractions.
so multiply the first one by (x+2)/(x+2) and the second by (x-1)/(x-1) and you should be able to algebretically get the rest:)
2006-11-06 19:53:24
·
answer #10
·
answered by munkmunk17 2
·
0⤊
2⤋